Potential Application of Green - Transit Oriented Development in the Giri Adipura Bus Station Area - Saspandi, Six; Widyastuti, Dyah Titisari (Universitas Syiah Kuala, 2025)
Green Transit Oriented Development (Green TOD) is a planning concept that combines city development with a public transportation system to form an environmentally friendly and sustainable environment. Green TOD integrates TOD with the principles of green urbanism to provide more significant environmental benefits (Niu et al., 2021). Giri Adipura Bus ation, as a type A Station and a center for public transportation such as AKDP, AKAP, BRT buses, public transportation and border transportation, has not been fully utilized by local residents as the main transit point for daily commuters to Solo and its surroundings. The high use of private vehicles is still visible (author's observations within a 400 meter radius), but data shows an increase in public bus and BRT users since they started operating (August 2023) with an occupancy rate of 99.65% (Edi Purwanto, Solopos.com, July 2024). This research aims to assess the potential of Giri Adipura Station as a Green TOD area and identify gaps with ideal Green TOD standards. Using a qualitative deductive approach, the research examined an area of 115.19 hectares in Kaliancar Subdistrict and Singodutan Village, Wonogiri, with a focus on a 400 meter radius from the Station as the core TOD zone and an 800 meter radius as a secondary area. Based on theoretical studies, Giri Adipura Station has the potential to become a rural/neighborhood TOD, with the level of gap aspects and causal factors as follows: Density + Green aspect, gap: KDB (33.1%), KLB (12%), population density (22.29%), number of residential units (13.3%), green certificate (100%). Cause: Regional development is delayed because city growth is concentrated in the district center, the research area is still in the early stages (affected by Station relocation and increasing the status of the Giri Adipura Station). The low level of green elements is due to high costs, minimal education, and lack of regulations/incentives. (Concentric Zone Theory, Urban Growth Theory, Growth Pole Theory. Aspects of Design for Walkability + Green, gaps: Block length (32.9%), pedestrian lanes (75%), no bicycle lanes, shade trees (50%), green facilities such as green roofs/gardens (100%). Causes: Settlements are formed naturally without careful planning, narrow/uphill roads, heavy traffic, violations of road borders, (Urban Design and Walkability Theory. Aspects of Destination to Transit + Green, gaps: Transit access is good (0%), but greenways and bicycle parking are not available (100%). Cause: Lack of synergy between agencies and low public understanding of the importance of green lanes. Destination Accessibility + Green, gaps: Green open space connectivity (100%), destination accessibility (0%).